EFEKTIVITAS TEKNIK RELAKSASI BENSON DALAM MENGURANGI INTENSITAS NYERI PADA WANITA PASCA OPERASI CAESAR DI RSU NURHAYATI GARUT TAHUN 2025 - Munawaroh, Fitroh; Wulandari, Ratna; Ginting, Agus Santi Br (Innovative: Journal Of Social Science Research, 2025)
Post-cesarean section (CS) pain is one of the main complaints that affect patient comfort and recovery process. Benson relaxation technique is a non-pharmacological method that helps reduce pain intensity. This study aims to determine the effectiveness of Benson relaxation technique in reducing pain intensity in women after CS surgery at Nurhayati Garut Hospital. The study design was a quasi-experimental with control group design with a sample of 30 respondents, divided into an intervention group given Benson relaxation technique using the Visual Analog Scale (VAS) instrument and a control group with standard care. The normality test used the Mann-Whitney U test. The results of the Mann-Whitney test showed a significant difference between the intervention group and the control group (p <0.001). With an average difference of -2.00 and a large effect size (1.00), the results of the study indicate that Benson relaxation technique has a strong impact on reducing pain intensity in women after CS surgery. Suggestion, Benson relaxation technique can be recommended as an effective non-pharmacological method in post-operative pain management